2020
DOI: 10.7181/acfs.2020.00290
|View full text |Cite
|
Sign up to set email alerts
|

Sensory recovery after infraorbital nerve avulsion injury

Abstract: The infraorbital nerve is a branch of the trigeminal nerve. Injury to the infraorbital nerve can be caused by trauma, including various facial fractures. Due to this nerve injury, patients complain of numbness and pain in the entire cheek, the ala of nose, and upper lip. In general, spontaneous sensory recovery is expected after decompressive surgery. If nerve transection is confirmed, however, neurorrhaphy is typically performed. Here, we present a case in which microsurgery was not performed in a patient wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…This study had some limitations. First, the duration of facial palsy in our cases ranged from 12 months to 27 years, which far exceeded the appropriate time for surgery and made it difficult to expect favorable recovery [ 19 , 20 ]. Second, as this was a retrospective study, it was not possible to control the number of patients per group.…”
Section: Discussionmentioning
confidence: 99%
“…This study had some limitations. First, the duration of facial palsy in our cases ranged from 12 months to 27 years, which far exceeded the appropriate time for surgery and made it difficult to expect favorable recovery [ 19 , 20 ]. Second, as this was a retrospective study, it was not possible to control the number of patients per group.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Felice et al (2020) reported an increased incidence of post-operative paraesthesia of the infraorbital nerves. Although brief, this unpleasant complication is likely to be a concern for patients as damage to the nerve may not just result in paraesthesia but may also be accompanied by pain in the lower eyelid, ala of the nose and upper lip (Lee et al, 2020). Appropriate surgical planning and surgical expertise can minimise this risk.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with anterior maxillary wall fracture, pain may occur if proper reconstruction is not performed, so it is necessary to differentiate it [ 8 ]. In the case of neuralgia, it is necessary to differentially diagnose the numbness of the entire cheek, the ala of nose, and the upper lip, which are the dominant regions of the infraorbital nerve due to midfacial bone fractures such as orbital wall fracture and zygomaticomaxillary fracture, which are common among facial bone fractures [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%